Social and structural determinants of youth alcohol use in Tanzania: The role of gender, social vulnerability and stigma. Issue 1 (2nd January 2021) - Sommer, Marni; Kaaya, Sylvia; Kajula, Lusajo; Marwerwe, Graca; Hamisi, Hassan; Parker, Richard
ABSTRACT: Adolescent alcohol use remains an under-addressed population health issue across Africa. Although the literature explores the intersection of alcohol use and vulnerability to HIV and AIDS, there is limited evidence on the gendered uptake and use of alcohol among adolescents. Capturing adolescents' voiced experiences about the societal influences shaping their alcohol usage is essential for identifying contextually relevant interventions to reduce their vulnerability to alcohol and related risky behaviours, such as unsafe sex. We conducted qualitative research in urban Tanzania, including key informant interviews, systematic mapping of alcohol availability, in-depth interviews with adolescents in and out of school and adults, and participatory methodologies with adolescents ages 15-19. The findings described here were drawn from the participatory methodologies ( n  = 177); and in-depth interviews with adolescents ( n  = 24) and adults ( n  = 24). Three key themes emerged: (1) boys' increased social vulnerability to alcohol consumption; (2) the ways in which stigma shapes girls' alcohol usage; and (3) how gendered perceptions of alcohol use reinforce societal inequalities. There exists an urgent need to address the social and gendered vulnerabilities of youth in Africa to the uptake and use of alcohol, and identify interventions that reshape notions of masculinity increasing boy's vulnerability to use.